Intramedullary Stress and Strain Correlate with Neurological Dysfunction in Degenerative Cervical Myelopathy - Mahmudur Rahman; Karthik Banurekha Devaraj; Omkar Chauhan; Balaji Harinathan; Narayan Yoganandan; Aditya Vedantam (Applied Sciences)
Degenerative cervical myelopathy (DCM) is characterized by progressive neurological dysfunction, yet the contribution of intramedullary stress and strain during neck motion remains unclear. This study used patient-specific finite element models (FEMs) of the cervical spine and spinal cord to examine the relationship between spinal cord biomechanics and neurological dysfunction. Twenty DCM patients (mean age 62.7 ± 11.6 years; thirteen females) underwent pre-surgical MRI-based modeling to quantify von Mises stress and maximum principal strains at the level of maximum spinal cord compression during simulated neck flexion and extension. Pre-surgical functional assessments included hand sensation, dexterity, and balance. During flexion, the mean intramedullary stress and strain at the level of maximum compression were 7.6 ± 3.7 kPa and 4.3 ± 2.0%, respectively. Increased intramedullary strain during flexion correlated with decreased right-hand sensation (r = −0.58, p = 0.014), impaired right-hand dexterity (r = −0.50, p = 0.048), and prolonged dexterity time (r = 0.52, p = 0.039). Similar correlations were observed with intramedullary stress. Patients with severe DCM exhibited significantly greater stress during flexion than those with mild/moderate disease (p = 0.03). These findings underscore the impact of dynamic spinal cord biomechanics on neurological dysfunction and support their potential utility in improving DCM diagnosis and management.